DO HEDONISM LIFESTYLE AND FINANCIAL LITERACY AFFECT TO STUDENT’S PERSONAL FINANCIAL MANAGEMENT? - Yana, Noven; Setyawan, Ignatius Roni (International Journal of Application on Economics and Business, 2023)
The purpose of this study was to determine the effect of Hedonism Lifestyle and Financial Literacy on Students' Personal Financial Management. The sample in this study was all university students, which in the end used the convenience sampling method to select the sample so that a sample of 81 students from the 2018 class of Faculty of Ecconomics and Business Tarumanagara University. The data analysis technique used is Structural Equation Modeling (SEM) employed by the Smart-PLS program. The results of this study are hedonism lifestyle and financial literacy have a significant influence on personal financial management.However, the hedonistic lifestyle has a different direction sign with financial literacy as a determining factor for students' personal financial management. The managerial implication of this research that occurs is that parents need to emphasize more financial literacy than the hedonistic lifestyle in order to form a better personal financial management attitude in the future.